Efficacy of Modified Atkins Ketogenic Diet in Chronic Cluster Headache: An Open-Label, Single-Arm, Clinical Trial - Di Lorenzo, Cherubino; Coppola, Gianluca; Di Lenola, Davide; Evangelista, Maurizio; Sirianni, Giulio; Rossi, Paolo; Di Lorenzo, Giorgio; Serrao, Mariano; Pierelli, Francesco (Frontiers in Neurology, 2018)
Introduction. Drug-resistant cluster headache (CH) is still an open clinical challenge. Recently, our group observed the clinical efficacy of a ketogenic diet (KD), usually adopted to treat drug-resistant epilepsies, on migraine. Aim. Here, we aim to detect the effect of KD in a group of drug-resistant chronic CH (CCH) patients. Materials and methods: Eighteen drug-resistant CCH patients underwent a 12-week KD (Atkins Modified Diet, MAD), and the clinical response was evaluated in terms of response (≥ 50% attacks reduction). Results. Of the 18 CCH patients, 15 were considered responders to the diet (11 experienced a full resolution of headache, and 4 had a headache reduction of at least 50% in terms of mean monthly number of attacks during the diet). The mean monthly number of attacks for each patient at the baseline was 108.71 (S.D.=81.71); at the end of the third month of diet, it was reduced to 31.44 (S.D.=84.61). Conclusions: We observed for the first time that a 3-month ketogenesis ameliorates clinical features of CCH. Registration: NCT03244735 ClinicalTrials.gov.